Electrode for electrolysis and electrolytic cell
By optimizing the molar ratio and crystallite size of ruthenium element to iridium element in the catalyst layer of the electrolytic electrode, and combining other metal elements, the problems of durability and electrolytic performance of the electrolytic electrode are solved, and low voltage and low power consumption are achieved The long-term electrolysis effect of quantity.
Patent Information
- Application Number
- CN202380036553.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-07
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-13
AI Technical Summary
The existing electrodes for electrolysis have room for improvement in improving the durability of the mixing ratio of ruthenium and iridium, especially in the long-term low voltage and low power consumption of salt electrolysis.
By forming a catalyst layer on the conductive substrate, the molar ratio of ruthenium element to iridium element in the catalyst layer is 1.4 or more, and the crystallite size observed in the X-ray diffraction measurement is 2θ=27° or more, 28.5° or less. Combined with the combination of other metal elements such as Zn, Cu, Co, V, Ga, Ni, Fe and Nb, the crystallite size and element ratio of the catalyst layer are optimized to improve electrolytic performance and durability.
It realizes the durability and electrolytic performance of the electrodes for electrolysis, reduces the overvoltage in the early stage of electrolysis, and maintains low voltage and low power consumption for a long time. It is suitable for various electrolysis processes, especially the ion exchange membrane method. Salt electrolysis.
Smart Images

Figure CN119137313A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode for electrolysis and an electrolytic cell. Background Art
[0002] Ion exchange membrane salt electrolysis refers to a method of producing sodium hydroxide, chlorine and hydrogen by using an electrolysis electrode to electrically decompose salt water (electrolyze). In the ion exchange membrane salt electrolysis process, a technology that can maintain a low electrolysis voltage for a long time is being sought in order to reduce power consumption. As an example of such a technology, Patent Document 1 proposes an electrode for electrolysis, which is an electrode for electrolysis having a conductive substrate and a catalyst layer formed on the surface of the conductive substrate, wherein the catalyst layer contains ruthenium, iridium, titanium, and at least one first transition metal element selected from the group consisting of Sc, V, Cr, Fe, Co, Ni, Cu and Zn, and the first transition metal element contained in the catalyst layer relative to 1 mole of the titanium element is 0.25 mol% or more and less than 3.4 mol%, and the D value of the electrolysis electrode as an indicator of double layer capacitance is 120C / m 2 Above 420C / m 2 the following.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6670948 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The electrode for electrolysis described in Patent Document 1 can reduce the overvoltage in the initial stage of electrolysis and can perform electrolysis at low voltage and low power consumption for a long time. On the other hand, further research by the present inventors has revealed that the electrode for electrolysis described in Patent Document 1 has room for improvement in terms of further improving the durability based on the mixing ratio of ruthenium element and iridium element.
[0008] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an electrode for electrolysis and the like which are excellent in durability and electrolytic performance.
[0009] Means for solving problems
[0010] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by using an electrode for electrolysis in which a predetermined crystallite size calculated for a catalyst layer is within a predetermined range, thereby completing the present invention.
[0011] That is, the present invention includes the following aspects. [1]
[0013] An electrode for electrolysis, comprising:
[0014] a conductive substrate; and
[0015] a catalyst layer disposed on the surface of the conductive substrate,
[0016] The electrode for electrolysis satisfies at least one of the following conditions (I) and (II):
[0017] (I) The catalyst layer contains ruthenium and iridium, and the crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is above the following.
[0018] (II) The above-mentioned catalyst layer contains: (i) ruthenium element; (ii) iridium element; and (iii) at least one metal element M selected from the group consisting of W, Zn, Mn, Cu, Co, V, Ga, Ta, Ni, Fe, Mo, Nb and Zr, and in the above-mentioned catalyst layer, the molar ratio of the above-mentioned ruthenium element to the above-mentioned iridium element is greater than 1.4 in terms of ruthenium element / iridium element, and in the above-mentioned catalyst layer, the molar ratio of the above-mentioned metal element M to the above-mentioned ruthenium element is greater than 0.06 and less than 3.5 in terms of metal element M / ruthenium element. [2]
[0020] The electrode for electrolysis as described in [1], which satisfies the above condition (II). [3]
[0022] The electrode for electrolysis as described in [2], wherein the crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is above the following. [4]
[0024] The electrode for electrolysis as described in [2] or [3], wherein the metal element M contains Zn, Mn, Cu, Co, V, Ga, Ni, Fe and / or Nb. [5]
[0026] The electrode for electrolysis as described in [1] satisfies the above condition (I). [6]
[0028] The electrode for electrolysis as described in [5], wherein in the catalyst layer, the molar ratio of the ruthenium element to the iridium element is 1.4 or more in terms of ruthenium element / iridium element. [7]
[0030] The electrode for electrolysis as described in [5] or [6], wherein
[0031] The catalyst layer contains the metal element M.
[0032] In the catalyst layer, a molar ratio of the metal element M to the ruthenium element is 0.05 to 3.5 in terms of metal element M / ruthenium element. [8]
[0034] The electrode for electrolysis as described in any one of [5] to [7], wherein the metal element M contains Zn, Mn, Cu, Co, V, Ga, Ni, Fe and / or Nb. [9]
[0036] An electrolytic cell comprising the electrolysis electrode according to any one of [1] to [8].
[0037] Effects of the Invention
[0038] According to the present invention, it is possible to provide an electrode for electrolysis and the like which are excellent in durability and electrolytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic cross-sectional view of an example of the electrolytic cell according to the present embodiment. DETAILED DESCRIPTION
[0040] The specific implementation mode of the present invention (also referred to as "the present implementation mode" in this specification) is described in detail below. The following implementation mode is an example for illustrating the present invention and is not intended to limit the present invention to the following content. The present invention can be implemented by appropriately deforming within the scope of its main points.
[0041] <Electrode for electrolysis>
[0042] The electrode for electrolysis of the present embodiment includes a conductive substrate and a catalyst layer disposed on the surface of the conductive substrate, and satisfies at least one of the following conditions (I) and (II):
[0043] (I) The catalyst layer contains ruthenium and iridium, and the crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is above the following.
[0044] (II) The above-mentioned catalyst layer contains: (i) ruthenium element; (ii) iridium element; and (iii) at least one metal element M selected from the group consisting of W, Zn, Mn, Cu, Co, V, Ga, Ta, Ni, Fe, Mo, Nb and Zr, and in the above-mentioned catalyst layer, the molar ratio of the above-mentioned ruthenium element to the above-mentioned iridium element is greater than 1.4 in terms of ruthenium element / iridium element, and in the above-mentioned catalyst layer, the molar ratio of the above-mentioned metal element M to the above-mentioned ruthenium element is greater than 0.06 and less than 3.5 in terms of metal element M / ruthenium element.
[0045] Since the electrode for electrolysis of the present embodiment is constructed as described above, it has excellent durability and electrolytic performance. It should be noted that the electrode for electrolysis of the present embodiment may satisfy only condition (I) or only condition (II), preferably at least condition (II), and more preferably both condition (I) and condition (II).
[0046] (Conductive substrate)
[0047] The electrode for electrolysis of the present embodiment has a conductive substrate. As the material of the conductive substrate, there is no particular limitation as long as it is a conductive material, and various known materials can be used, among which valve metals are preferred. When a valve metal is used, there is a tendency for the corrosion resistance of the electrode for electrolysis to be improved, and it can be preferably used in a highly concentrated salt water near saturation or in an atmosphere where chlorine is generated. As valve metals, for example, titanium, tantalum, niobium, zirconium, etc. can be cited but are not limited to. From the aspects of economy and affinity with the catalyst layer, titanium is preferred.
[0048] The shape of the conductive substrate is not particularly limited, and an appropriate shape can be selected according to the purpose. For example, an expanded shape, a porous plate, a metal mesh, etc. are suitable. The thickness of the conductive substrate is preferably 0.1 to 2 mm.
[0049] Regarding the contact surface of the conductive substrate with the catalyst layer, in order to improve the adhesion with the catalyst layer, it is preferred to perform a surface area enlargement treatment. As a method for the surface area enlargement treatment, for example, sandblasting using cut wire, steel mesh, alumina mesh, etc., and acid treatment using sulfuric acid or hydrochloric acid, etc. can be cited but not limited to. Among these treatments, a method in which the surface of the conductive substrate is formed with unevenness by sandblasting and then further acid treatment is performed.
[0050] (Catalyst layer)
[0051] The electrolysis electrode of this embodiment includes a catalyst layer disposed on the surface of a conductive substrate. The catalyst layer contains ruthenium and iridium as essential elements. In addition, the catalyst layer may optionally contain other elements.
[0052] Ruthenium acts as a main catalyst, and iridium contributes to durability.
[0053] The ruthenium element and the iridium element are preferably in the form of oxides, respectively. Examples of ruthenium oxides include, but are not limited to, RuO2, etc. Examples of iridium oxides include, but are not limited to, IrO2, etc.
[0054] The presence state of the ruthenium element and the iridium element in the catalyst layer is not particularly limited, but is preferably a solid solution of ruthenium oxide and iridium oxide.
[0055] In the catalyst layer, the ratio (molar ratio) of ruthenium to iridium is preferably 1.4 or more in terms of ruthenium / iridium. By making the ratio of the two elements in the above range, there is a tendency that the long-term durability of the electrolysis electrode is further improved. In addition, from the perspective of the voltage and durability of the catalyst layer, the ratio is more preferably 1.4 or more and 120 or less in terms of ruthenium / iridium, more preferably 1.4 or more and 100 or less, more preferably 1.4 or more and 60 or less, more preferably 1.4 or more and 30 or less, and more preferably 1.4 or more and 20 or less.
[0056] On the other hand, from the viewpoint of economic efficiency, the content ratio of ruthenium element / iridium element is more preferably 2.2 or more, further preferably 2.5 or more, and further preferably 2.6 or more.
[0057] In addition, from the same aspect as above, the content ratio of other elements (elements other than ruthenium and iridium) is preferably 0.1 to 25, more preferably 0.1 to less than 15, more preferably 0.1 to less than 8.0, in terms of other elements / iridium. Iridium, ruthenium and other elements may also be contained in the catalyst layer in a form other than oxides, for example, in the form of metal elements.
[0058] In this embodiment, from the perspective of balancing the voltage and durability of the catalyst layer, the other elements preferably include at least one metal element M selected from the group consisting of W, Zn, Mn, Cu, Co, V, Ga, Ta, Ni, Fe, Mo, Nb and Zr. The metal element M more preferably includes Zn, Mn, Cu, Co, V, Ga, Ni, Fe and / or Nb, further preferably includes Zn, Cu, Co, V, Ga, Ni and / or Fe, and further preferably includes Zn, Cu and / or V.
[0059] In the present embodiment, from the aspect of both the voltage and durability of the catalyst layer, the catalyst layer further comprises a metal element M, and the molar ratio of the metal element M to the ruthenium element is preferably 0.05 to 3.5, more preferably 0.06 to 3.5, further preferably 0.1 to 3.5, further preferably 0.1 to 0.6, and further preferably 0.1 to 0.2. It should be noted that when the metal element M comprises V, the molar ratio of V to the ruthenium element is preferably 0.05 to 0.15, more preferably 0.05 to 0.1, based on V / ruthenium element.
[0060] In the present embodiment, other elements may include tin, platinum, rhodium, etc. in addition to the above elements, but are not limited to these. As the existence form of these metal elements, for example, the existence in the form of metal elements contained in oxides can be cited. In the case where the catalyst layer in the present embodiment includes tin, platinum and / or rhodium, as the total amount thereof, the molar ratio of these metal elements to all metal elements contained in the catalyst layer is preferably 20 mol% or less, more preferably 10 mol% or less.
[0061] In this embodiment, the crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is preferably above The crystallite size can be said to be an indicator of whether ruthenium and iridium are dispersed as appropriate crystals in the catalyst layer as a whole. Specifically, in the range of 2θ=27° to 28.5°, peaks from the (110) plane of RuO2 and the (110) plane of IrO2 are observed, and the narrower the half-width of the peak, the more the crystallite size tends to increase.
[0062] The crystallite size is In the above case, the crystallinity of ruthenium and iridium can be appropriately increased, so there is a tendency to ensure durability. In addition, the above crystallite size is In the case of the following conditions, the crystal size of ruthenium and iridium can be appropriately reduced, and in this case, there is a tendency to prevent the durability of the catalyst layer as a whole from being reduced due to, for example, excessive separation from other elements. above In the following cases, the crystallization of ruthenium and iridium can be preferably controlled, and as a result, there is a tendency to show high durability even when the amount of iridium that contributes to durability is reduced. Regarding its mechanism of action, although it is not intended to be limited as follows, it is speculated as follows based on the research of the present inventors.
[0063] In the electrode for electrolysis of the present embodiment, when the crystallite size is controlled within a predetermined range, it is considered that at least the ruthenium element and the iridium element are equally distributed and easily mixed in the catalyst layer. It is considered that in particular, the ruthenium as the main catalyst and the iridium that imparts durability are uniformly mixed in the catalyst layer, whereby each element exhibits performance with higher efficiency, and the electrode for electrolysis can achieve high durability while maintaining a low overvoltage.
[0064] From the same perspective as above, the crystallite size is preferably above The following, more preferably above the following.
[0065] The crystallite size can be measured according to the method described in Examples below.
[0066] For example, the crystallite size can be adjusted to the above-mentioned range by adjusting the molar ratio of ruthenium element to iridium element to the above-mentioned preferred range, and / or adjusting the molar ratio of metal element M / ruthenium element to the above-mentioned preferred range. From the aspect of adjusting the above-mentioned crystallite size, specifically, for example, the molar ratio of ruthenium element / iridium element can be adjusted to be between 1.4 and 9.0, or the molar ratio of metal element M / ruthenium element can be adjusted to be between 0.06 and 3.5, but it is not limited thereto. In addition, the above-mentioned crystallite size can also be adjusted by, for example, the amount of ruthenium element, iridium element and metal element M in the catalyst layer. For example, from making the above-mentioned crystallite size be above From the following aspects, when all the metal elements contained in the catalyst layer are taken as 100 mass %, the total amount of the ruthenium element, the iridium element and the metal element M is preferably greater than 70 mass %, and more preferably 100 mass %.
[0067] The thickness of the catalyst layer in this embodiment is preferably 0.1 to 5 μm, more preferably 0.5 to 3 μm. By making the thickness of the catalyst layer above the lower limit, there is a tendency to be able to fully maintain the initial electrolysis performance. In addition, by making the thickness of the catalyst layer below the upper limit, there is a tendency to obtain an electrolysis electrode with excellent economic efficiency.
[0068] The catalyst layer may consist of only one layer or may consist of two or more layers.
[0069] When the catalyst layer is two or more layers, at least one of the layers satisfies at least one of the conditions (I) and (II). When the catalyst layer is two or more layers, for example, at least one layer may be equivalent to the catalyst layer in the present embodiment (a catalyst layer satisfying at least one of the conditions (I) and (II)). The catalyst layer in the present embodiment may be in a form having two or more layers with the same composition or different compositions.
[0070] When the catalyst layer has two or more layers, the thickness of the catalyst layer in the present embodiment is also preferably 0.1 to 5 μm, more preferably 0.5 to 3 μm, as described above.
[0071] In the present embodiment, the elements constituting the catalyst layer, i.e., ruthenium, iridium, and other optional elements are preferably uniformly dispersed in the catalyst layer. When all these elements are uniformly dispersed, there is also a tendency that, in particular, ruthenium as the main catalyst, iridium imparting durability, and other elements having various other functions respectively exhibit performance with higher efficiency, and the electrolysis electrode can achieve high durability while maintaining a low overvoltage.
[0072] In the present embodiment, for example, by controlling the crystallite size within the above-mentioned range, making the catalyst layer contain a metal element M, adjusting the molar ratio of the ruthenium element to the iridium element to a preferred range, and / or adjusting the sintering temperature described later to a preferred range, at least the ruthenium element and the iridium element tend to be more evenly dispersed in the catalyst layer.
[0073] The distribution of elements in the catalyst layer can be measured by using energy dispersive X-ray spectroscopy, etc. When the catalyst layer has two or more layers, the ruthenium element, iridium element, and other optional elements contained in the catalyst layer in this embodiment can be uniformly dispersed in at least one of the layers, and the ruthenium element, iridium element, and other optional elements can also be uniformly dispersed in all catalyst layers.
[0074] (Method for producing an electrolytic electrode)
[0075] Next, an example of a method for producing the electrode for electrolysis according to the present embodiment will be described in detail.
[0076] The electrode for electrolysis of the present embodiment can be manufactured by, for example, forming a catalyst layer comprising ruthenium, iridium and other optional elements on a conductive substrate. Here, the conductive substrate can be a substrate to which the above-mentioned surface area enlargement treatment has been implemented. In addition, the formation of the catalyst layer is preferably carried out by thermal decomposition. In the manufacturing method based on the thermal decomposition method, after a coating liquid containing a mixture of compounds (precursors) containing the above-mentioned elements is applied to a conductive substrate, it is fired under an oxygen-containing atmosphere to thermally decompose the components in the coating liquid, thereby forming a catalyst layer. According to this method, the electrode for electrolysis can be manufactured with high productivity using fewer steps than the existing manufacturing method.
[0077] Thermal decomposition as used herein refers to the process of firing a metal salt as a precursor, etc., under an oxygen-containing atmosphere to decompose into metal oxides or metals and gaseous substances. The decomposition products obtained can be controlled by the type of metal contained in the precursor mixed into the coating liquid as a raw material, the type of metal salt, the atmosphere for thermal decomposition, etc. Usually, under an oxidizing atmosphere, many metals have a tendency to easily form oxides. In the industrial manufacturing process of electrodes for electrolysis, thermal decomposition is usually carried out in the air. In the present embodiment, the range of oxygen concentration during firing is not particularly limited, and it can be carried out in the air. In the present embodiment, air or oxygen can be circulated in the firing furnace as needed.
[0078] As a preferred method for manufacturing an electrode for electrolysis of the present embodiment, it is preferred to have the following steps: a step of preparing a coating liquid containing a ruthenium compound, an iridium compound, and optionally a compound containing other elements; a step of applying the coating liquid to at least one side of a conductive substrate to form a coating film; and a step of firing the coating film in an oxygen-containing atmosphere to form a catalyst layer. It should be noted that the ruthenium compound, the iridium compound, and the compound containing other elements correspond to precursors containing the metal elements contained in the catalyst layer in the present embodiment. The above method can manufacture an electrode for electrolysis having a uniform catalyst layer.
[0079] In the compound contained in the coating solution, the ruthenium compound and the iridium compound can be oxides, but are not limited thereto, and for example, can also be metal salts, etc. As these metal salts, for example, chlorides, nitrates, dinitroso diamine complexes, nitroso nitrates, sulfates, acetates, and metal alkoxides can be cited, but are not limited thereto. As the metal salt of the ruthenium compound, for example, ruthenium chloride, ruthenium nitrate, etc. can be cited, but are not limited thereto. As the metal salt of the iridium compound, for example, iridium chloride, iridium nitrate, etc. can be cited, but are not limited thereto. In the present embodiment, from the aspect of durability, the metal salt of the ruthenium compound and the iridium compound is preferably a nitrate.
[0080] Among the compounds contained in the coating solution, the compound containing other elements may be an oxide, but is not limited thereto. With regard to the compound containing other elements, taking cobalt as an example, it may be an oxygen-containing acid of cobalt and its salt, a chloride of cobalt, or a nitrate of cobalt. As the counter cation in the above-mentioned oxygen-containing acid salt, for example, Li + 、Na + , K + , Ca 2+ Etc. Specific examples of such compounds are not limited to the following examples, but examples of oxoacids and salts thereof include lithium cobaltate, sodium cobaltate, etc., examples of chlorides include cobalt chloride, etc., and examples of nitrates include cobalt nitrate, etc.
[0081] The above compounds are appropriately selected and used according to the desired metal element ratio in the catalyst layer. The coating liquid may further include, but is not limited to, metal compounds containing metal elements such as tantalum, niobium, tin, platinum, rhodium, or organic compounds containing metal elements such as tantalum, niobium, tin, platinum, rhodium, etc. The coating liquid is preferably a liquid composition in which the above compound group is dissolved or dispersed in a suitable solvent. The solvent of the coating liquid used here can be selected according to the type of the above compound. For example, water; alcohols such as butanol, etc. can be used. The total compound concentration in the coating liquid is not particularly limited, and is preferably 10 to 150 g / L from the perspective of appropriately controlling the thickness of the catalyst layer.
[0082] As a method for applying the coating liquid to the surface on the conductive substrate, for example, but not limited to: an immersion method in which the conductive substrate is immersed in the coating liquid; a method of applying the coating liquid to the surface of the conductive substrate using a brush; a roller method in which the conductive substrate passes through a sponge-like roller impregnated with the coating liquid; an electrostatic coating method in which the conductive substrate and the coating liquid are oppositely charged and sprayed; and the like. Among these coating methods, the roller method and the electrostatic coating method are preferred from the perspective of excellent industrial productivity. Through these coating methods, a coating film of the coating liquid can be formed on at least one side of the conductive substrate. After the coating liquid is applied to the conductive substrate, it is preferably carried out as needed to dry the coating film. Through this drying process, a catalyst layer can be formed more firmly on the surface of the conductive substrate. The drying conditions can be appropriately selected according to the composition of the coating liquid, the type of solvent, etc. The drying process is preferably carried out at a temperature of 10 to 90°C for 1 to 20 minutes.
[0083] After forming a coating film of the coating liquid on the surface of the conductive substrate, it is fired in an oxygen-containing atmosphere. The firing temperature can be appropriately selected according to the composition of the coating liquid and the type of solvent. The firing temperature is preferably 300-650°C. When the firing temperature is above 300°C, there is a tendency to promote the decomposition of precursors such as ruthenium compounds and to easily obtain a desired catalyst layer containing ruthenium oxide, etc. When the firing temperature is below 650°C, there is a tendency to prevent oxidation of the conductive substrate and improve the adhesion of the interface between the catalyst layer and the conductive substrate. In particular, when a titanium substrate is used as a conductive substrate, it is preferred to consider the above tendency to make the firing temperature 300-650°C. In addition, it is preferred that the firing time is long. On the other hand, from the perspective of the productivity of the electrode, it is preferred to adjust the firing time so that it will not be too long. From the above aspects, the firing time for each time is preferably 5 to 60 minutes.
[0084] The steps of coating, drying and firing of the catalyst layer can be repeated as needed to form the catalyst layer to a desired thickness. After the catalyst layer is formed, it can also be fired for a longer time as needed to further improve the stability of the catalyst layer which is extremely stable in chemical, physical and thermal aspects. As a condition for long-term firing, it is preferably fired at 400 to 650° C. for about 30 minutes to 4 hours.
[0085] The electrolysis electrode of the present embodiment also has low overvoltage in the initial stage of electrolysis, and can perform electrolysis at low voltage and low power consumption for a long time. Therefore, it can be used for various electrolysis. In particular, it is preferably used as an anode for chlorine generation, and more preferably used as an anode for salt electrolysis of an ion exchange membrane method.
[0086] <Electrolyzer>
[0087] The electrolytic cell of this embodiment is provided with the electrolysis electrode of this embodiment. This electrolytic cell reduces the initial voltage when performing electrolysis. A cross-sectional schematic diagram of an example of the electrolytic cell of this embodiment is shown in Figure 1 .
[0088] The electrolytic cell 200 includes an electrolyte 210, a container 220 for accommodating the electrolyte 210, an anode 230 and a cathode 240 immersed in the electrolyte 210, an ion exchange membrane 250, and a wiring 260 for connecting the anode 230 and the cathode 240 to a power supply. Here, the space on the anode side separated by the ion exchange membrane 250 in the electrolytic cell 200 is called an anode chamber, and the space on the cathode side is called a cathode chamber. The electrolytic cell of this embodiment can be used for various electrolysis. Hereinafter, as a representative example, the case of using for electrolysis of an alkali metal chloride aqueous solution is described. As the electrolyte 210 supplied to the electrolytic cell of this embodiment, for example, an alkali metal chloride aqueous solution such as a sodium chloride aqueous solution (salt water) of 2.5 to 5.5 equivalents (N) or a potassium chloride aqueous solution can be used in the anode chamber, and a diluted alkali metal hydroxide aqueous solution (such as a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, etc.) or water can be used in the cathode chamber.
[0089] As the anode 230, the electrode for electrolysis of the present embodiment can be used. As the ion exchange membrane 250, for example, a fluororesin membrane having an ion exchange group can be used. As a specific example, but not limited to, "Aciplex" (registered trademark) F6801 (manufactured by Asahi Kasei Corporation) and the like can be cited. As the cathode 240, an electrode coated with a catalyst on a conductive substrate as a cathode for hydrogen generation can be used. As the cathode, a well-known cathode can be used, specifically, for example, a cathode formed by coating nickel, nickel oxide, an alloy of nickel and tin, a combination of activated carbon and an oxide, ruthenium oxide, platinum, etc. on a nickel substrate; a cathode formed by forming a coating of ruthenium oxide on a nickel metal mesh substrate; and the like.
[0090] The structure of the electrolytic cell of the present embodiment is not particularly limited, and it can be a monopolar type or a bipolar type. The material constituting the electrolytic cell is not particularly limited. For example, as the material of the anode chamber, titanium that is resistant to alkali metal chlorides and chlorine is preferred, and as the material of the cathode chamber, nickel that is resistant to alkali metal hydroxides and hydrogen is preferred. The electrode for electrolysis (anode 230) of the present embodiment can be configured with an appropriate gap between it and the ion exchange membrane 250, or it can be configured in contact with the ion exchange membrane 250. The cathode 240 can be configured with an appropriate gap between it and the ion exchange membrane 250, or it can be a contact type electrolytic cell (zero-gap electrolytic cell) with no gap between it and the ion exchange membrane 250. There are no particular limitations on the electrolysis conditions of the electrolytic cell of the present embodiment, and it can be operated under known conditions. For example, it is preferred to adjust the electrolysis temperature to 50-120°C and the current density to 0.5-10 kA / m 2 To perform electrolysis.
[0091] By applying the electrode for electrolysis of the present embodiment to an electrolytic cell, the electrolysis voltage in the electrolysis of salt can be reduced compared with the past. Therefore, by using the electrolytic cell of the present embodiment equipped with the electrode for electrolysis, the power consumption required for the electrolysis of salt can be reduced. In addition, the electrode for electrolysis of the present embodiment has a catalyst layer that is stable in chemical, physical and thermal aspects, and therefore has excellent long-term durability. Therefore, by using the electrolytic cell of the present embodiment equipped with the electrode for electrolysis, the catalytic activity of the electrode can be maintained at a high level for a long time, and high-purity chlorine can be stably produced.
[0092] Example
[0093] The present embodiment will be described in more detail below based on examples, but the present embodiment is not limited to these examples.
[0094] First, each evaluation method in Examples and Comparative Examples is shown below.
[0095] (Ion exchange membrane salt electrolysis test)
[0096] As an electrolysis unit, an electrolysis unit including an anode unit having an anode chamber and a cathode unit having a cathode chamber was prepared. The electrolysis electrodes prepared in each example and comparative example were cut into a predetermined size (48×58 mm=0.002784 mm). 2 ) is made into a test electrode, which is installed on the rib of the anode chamber of the anode unit by welding and used as an anode. As a cathode, a cathode coated with a ruthenium oxide catalyst on a nickel metal mesh substrate is used. First, a metal nickel expanded substrate as a collector is cut into the same size as the anode and welded to the rib of the cathode chamber of the cathode unit, and then a buffer pad made of nickel wire is placed, and a cathode is arranged thereon. As a gasket, a rubber gasket made of EPDM (ethylene propylene diene rubber) is used, and an ion exchange membrane is sandwiched between the anode unit and the cathode unit. As the ion exchange membrane, a cation exchange membrane "Aciplex" (registered trademark) F6801 (manufactured by Asahi Kasei Corporation) for salt electrolysis is used.
[0097] In order to measure the chlorine overvoltage, the coating of the front end of the platinum wire coated with PFA (tetrafluoroethylene perfluoroalkoxyethylene copolymer) is removed to expose the platinum, and the obtained platinum wire is connected and fixed to the surface of the anode on the opposite side of the ion exchange membrane using a polytetrafluoroethylene wire, and used as a reference electrode. In the electrolysis test, the reference electrode reaches a saturated atmosphere due to the generated chlorine gas, so it shows the chlorine generation potential. Therefore, the potential of the reference electrode is subtracted from the potential of the anode, and the obtained value is evaluated as the chlorine overvoltage of the anode. The chlorine overvoltage is measured 1 day after the start of electrolysis (recorded as "chlorine overvoltage_start[mV]" in Table 2) and 21 days after the start of electrolysis (recorded as "chlorine overvoltage_end[mV]" in Table 2).
[0098] Regarding the electrolysis conditions, at a current density of 6 kA / m 2 Electrolysis was performed under the conditions of a brine concentration of 205 g / L in the anode unit, a NaOH concentration of 32 mass % in the cathode unit, and a temperature of 90° C. As a rectifier for electrolysis, “PAD110-32LA” (manufactured by Kikusui Electronics Industry Co., Ltd.) was used.
[0099] In addition, the Ru residual rate in the catalyst layer in the test electrode after electrolysis is calculated using the numerical values obtained by fluorescent X-ray measurement (XRF) of each metal component before and after electrolysis (100×content before electrolysis / content after electrolysis; %). As an XRF measuring device, Niton XL3t-800 or XL3t-800s (trade name, manufactured by Thermo Scientific) is used. In addition, the "Ru residual rate / (Ir / Ru)" is calculated by dividing the Ru residual rate obtained above by the molar ratio of iridium element to ruthenium element (Ir / Ru) in the coating liquid. The value of Ru residual rate / (Ir / Ru) is an indicator of how much catalyst remains after electrolysis relative to Ir / Ru. If the value is large, it is evaluated as a catalyst layer with a small amount of Ir and high durability.
[0100] (Calculation of crystallite size)
[0101] In order to calculate the crystallite size, the electrode was subjected to X-ray diffraction measurement (XRD). The XRD measurement device used was Rigaku MiniFlex600-C. The measurement was carried out under the following conditions; the X-ray source was Cu-Kα; the Soller slit on the incident side was 2.5°; the divergence slit was 1.25°; the Soller slit on the light-receiving side was 2.5°; the light-receiving slit was open; a Kβ filter was applied on the light-receiving side; the measurement range of 2θ was 18 to 60°; the step width was 0.02°; the scanning speed was 5° / min, and the sample (the above-mentioned test electrode was further cut into 16mm×16mm=0.000256m 2 The obtained sample was placed on a rotating sample table and measured while rotating the sample at a rotation speed of 60 rpm.
[0102] The calculation of the crystallite size is performed using the accompanying software SmarLab StudioII. The spectrum obtained by XRD measurement is read in using SmarLab StudioII, and peak fitting is performed under the conditions of peak shape; segmented pseudo-Voigt function, background type; B-spline. The crystallite size is calculated using the following Scherrer formula based on the peak with 2θ of 27-28.5°. It should be noted that when two or more peaks overlap within this range, the crystallite size obtained from the peak with the higher peak height is used. Since peaks from the (110) plane of RuO2 and the (110) plane of IrO2 are observed in the range of 2θ of 27-28.5°, the physical properties of the catalyst layer are compared by extracting the crystallite size from the peaks in this range.
[0103] Scherrer formula: Crystallite size = K × λ / (β × cosΘ)
[0104] K: Scherrer constant = 0.94
[0105] λ: Cu Kα ray = 0.15418 nm
[0106] β: Half peak width
[0107] Θ: Bragg angle
[0108] [Example 1]
[0109] As the conductive substrate, a titanium expanded substrate having a mesh size (LW) of 6 mm, a mesh size (SW) of 3 mm, and a plate thickness of 1.0 mm was used. The expanded substrate was fired at 540° C. for 4 hours in the atmosphere to form an oxide film on the surface, and then acid-treated in 25 mass % sulfuric acid at 85° C. for 4 hours to perform a pretreatment for providing fine concavo-convex on the surface of the conductive substrate.
[0110] Next, an aqueous ruthenium nitrate solution (manufactured by Furuya Metal Co., Ltd., ruthenium concentration of 100 g / L), an aqueous iridium chloride solution (manufactured by Tanaka Kikinzoku Co., Ltd., iridium concentration of 100 g / L), zinc chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade), and cobalt (II) nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade) were mixed so that the element ratio (molar ratio) of ruthenium, iridium, zinc, and cobalt was 65:25:5:5 to obtain an aqueous solution having a total metal concentration of 100 g / L, namely, coating liquid A1.
[0111] The coating liquid A1 is injected into a liquid receiving tank made of polyvinyl chloride, and the impregnated coating liquid 1 is absorbed by rotating the first sponge roller made of EPDM. The second sponge roller made of EPDM is arranged in a manner to contact the upper part of the first sponge roller. The PVC roller is further arranged in a manner to contact the upper part of the second sponge roller. Thereafter, the conductive substrate subjected to the pretreatment is passed between the second EPDM sponge roller and the above-mentioned PVC roller for coating. Thereafter, after drying at 50°C for 10 minutes, it is fired at 400°C for 10 minutes in the atmosphere (recorded as "firing temperature (first time; °C)" in Table 1). The firing temperature was raised to 450°C, and the cycle consisting of the above-mentioned roller coating, drying and firing was further repeated three times (recorded as "firing temperature (2nd-4th times; °C)" in Table 1), and finally, the firing was further carried out at 520°C for 1 hour (recorded as "firing temperature (PB; °C)" in Table 1), thereby forming a black-brown catalyst layer on the conductive substrate to prepare an electrode for electrolysis.
[0112] The electrode for electrolysis of Example 1 was subjected to the above-mentioned XRD measurement. As a result, the crystallite size was In addition, the electrolysis electrode of Example 1 was subjected to the above electrolysis test. As a result, the Ru residual ratio / (Ir / Ru) was large, 260, and it was evaluated as an electrode having a catalyst layer with a small amount of Ir and high durability. The same test was also conducted. As a result, the chlorine overvoltage was 47 mV one day after the start of electrolysis, and the chlorine overvoltage was 46 mV 21 days after the start of electrolysis, both of which were sufficiently low levels.
[0113] [SEM / EDX analysis]
[0114] In addition, the cross section of the catalyst layer is analyzed using energy dispersive X-ray spectroscopy (SEM / EDX analysis). As the analysis object, the catalyst layer corresponding to the position of the current-carrying surface during the electrolysis of the above-mentioned salt in the catalyst layer in the electrolysis electrode is used as the object, and the part where the peeling of the catalyst and the attachment of impurities such as organic matter are not observed is further selected, and the cross section of the catalyst layer of the part is used as the analysis object. According to the obtained image, it is confirmed that the ruthenium element and the iridium element are distributed in the catalyst layer in the same manner and are evenly mixed. The details of the analysis conditions are as described below.
[0115] Device: Regulus SU8220 (manufactured by Hitachi High-Technologies Corporation) and Flat QUAD5060 (manufactured by Bruker Corporation)
[0116] Observation conditions (SEM): Acceleration voltage 10 kV, detector SE (U), emission current 10 uA, capacitor lens 1 setting 5, probe current setting: Norm, working distance 11 mm
[0117] Observation conditions (EDX): Integration time 1,000s, Duel time 8μs, Window type 1+2μm Mylar
[0118] The specific operations of the analysis are as follows.
[0119] (1) Set the magnification on the SEM control screen to 10,000x.
[0120] (2) Set the image resolution on the EDX side to 1600×1200 pixels.
[0121] (3) In the EDX signal capture operation, the mapping area was selected as “Fixed”, and the mapping width and the mapping height were set to 800 points and 600 points, and the EDX measurement was carried out.
[0122] (4) Regarding the EDX measurement results, select “Tile size 2×2” and perform quantitative analysis using the interactive mode.
[0123] (5) For the deconvolution setting during quantitative analysis, select “Series fit” and for the quantitative analysis mode, select [P / B-ZAF].
[0124] (6) The elements selected for quantitative analysis are "ruthenium, iridium, zinc, and cobalt" and an EDX network sum image is obtained. It should be noted that in this quantitative analysis, the elements to be analyzed can be changed according to the types of elements constituting the catalyst layer to adjust the conditions as appropriate.
[0125] [Calculation of cosine similarity]
[0126] In order to remove the area of the analysis image that does not contain ruthenium or iridium at all, pixels with a brightness value of 50 or more in at least one of the EDX images for ruthenium and iridium are used as the analysis area. The analysis area is defined as ROI (Region Of Interest), and the consistency of the distribution of Ru and Ir in the ROI is calculated using the following method.
[0127] In the EDX images of ruthenium and iridium, the pixels of the ROI are expanded into a one-dimensional vector, and the cosine similarity of the two vectors is calculated. At this time, each pixel position corresponds to each dimension of the vector, and the brightness value of each pixel corresponds to the element of the corresponding dimension. The closer the cosine similarity is to 1, the more it means that the EDX images of Ru and Ir are similar, that is, Ru and Ir are distributed in the same way in the catalyst layer and are evenly mixed.
[0128] The cosine similarity of Example 1 obtained as described above is 0.97, indicating that ruthenium and iridium are distributed similarly in the catalyst layer.
[0129] [Evaluation results]
[0130] As described above, in the electrode for electrolysis of Example 1, the crystallite size is controlled within a specified range, and the result is evaluated as excellent in durability and electrolytic performance. In addition, the results of SEM / EDX analysis of ruthenium and iridium indicate that by satisfying at least one of the conditions (I) and (II) in the present embodiment, there is a tendency that the ruthenium element and the iridium element are equally distributed and uniformly mixed in the catalyst layer.
[0131] [Examples 2 to 23 and Comparative Examples 1 to 6]
[0132] The composition of the coating liquid A1 is changed in such a way that the catalyst layer becomes the metal composition shown in Table 1; the firing temperature (1st time; ℃) is changed to the value recorded in Table 1; the firing temperature (2nd to 4th times; ℃) is changed to the value recorded in Table 1; and / or the firing temperature (PB; ℃) is changed to the value recorded in Table 1. Except for this, the electrode for electrolysis is prepared in the same manner as in Example 1.
[0133] The constitution of the electrolytic electrodes prepared in Examples 1 to 23 and Comparative Examples 1 to 6 (the metal composition of the coating solution used in the formation of the catalyst layer) and various evaluation results of the electrolytic electrodes are shown in Tables 1 to 2. The unit of the numerical value of the metal composition in the table is "mol %", which means the molar percentage (feed ratio) of all metal elements contained in the catalyst layer. In addition, the value of ruthenium element / iridium element (Ru / Ir) and the value of metal element M / ruthenium element (M / Ru) refer to the values calculated from the feed ratio.
[0134]
[0135] [Table 2]
[0136]
[0137] The electrolytic electrodes of Examples 8 and 12 were also subjected to the same SEM / EDX analysis as in Example 1. As a result, the cosine similarity of Example 8 was 0.94, and the cosine similarity of Example 12 was 0.93. Based on these results, it was confirmed that the ruthenium element and the iridium element were uniformly distributed in the catalyst layer in Examples 8 and 12 as in Example 1.
[0138] Separately, the electrolysis electrode of Comparative Example 1 was subjected to the same SEM / EDX analysis as Example 1. As a result, the cosine similarity of Comparative Example 1 was 0.89. From this result, it was confirmed that in Comparative Example 1, the distribution states of the ruthenium element and the iridium element in the catalyst layer were different, and at least one of the ruthenium element and the iridium element was unevenly present in the catalyst layer.
[0139] These results also suggest that by satisfying at least one of the conditions (I) and (II) in the present embodiment, there is a tendency for the ruthenium element and the iridium element to be uniformly distributed in the catalyst layer.
[0140] This application is based on the Japanese patent application filed on June 20, 2022 (Japanese Patent Application No. 2022-098944) and the Japanese patent application filed on April 7, 2023 (Japanese Patent Application No. 2023-062983), and these contents are introduced into this article as a reference.
[0141] Explanation of symbols
[0142] 200 electrolytic cell
[0143] 210 electrolyte
[0144] 220 containers
[0145] 230 Anode (electrode for electrolysis)
[0146] 240 cathode
[0147] 250 ion exchange membrane
[0148] 260 wiring
Claims
1. An electrode for electrolysis, comprising: Conductive substrate ; as well as a catalyst layer disposed on the surface of the conductive substrate, The electrode for electrolysis satisfies at least one of the following conditions (I) and (II): (I) the catalyst layer contains ruthenium and iridium, and the crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is above the following; (II) The catalyst layer comprises: (i) ruthenium element; (ii) iridium element; and (iii) at least one metal element M selected from the group consisting of W, Zn, Mn, Cu, Co, V, Ga, Ta, Ni, Fe, Mo, Nb and Zr, and in the catalyst layer, the molar ratio of the ruthenium element to the iridium element is greater than 1.4, calculated as ruthenium element / iridium element, and in the catalyst layer, the molar ratio of the metal element M to the ruthenium element is greater than 0.06 and less than 3.5, calculated as metal element M / ruthenium element.
2. The electrode for electrolysis according to claim 1, which satisfies the condition (II).
3. The electrode for electrolysis according to claim 2, in, The crystallite size calculated from the peak observed in the range of 2θ=27° to 28.5° in the XRD spectrum obtained by subjecting the catalyst layer to X-ray diffraction measurement is: above the following.
4. The electrode for electrolysis according to claim 2, in, The metal element M includes Zn, Mn, Cu, Co, V, Ga, Ni, Fe and / or Nb.
5. The electrode for electrolysis according to claim 1, which satisfies the condition (I).
6. The electrode for electrolysis according to claim 5, in, In the catalyst layer, a molar ratio of the ruthenium element to the iridium element is 1.4 or more in terms of ruthenium element / iridium element.
7. The electrode for electrolysis according to claim 5, in, The catalyst layer comprises the metal element M, In the catalyst layer, a molar ratio of the metal element M to the ruthenium element is 0.05 or more and 3.5 or less in terms of metal element M / ruthenium element.
8. The electrode for electrolysis according to claim 7, in, The metal element M includes Zn, Mn, Cu, Co, V, Ga, Ni, Fe and / or Nb. 9 . An electrolytic cell comprising the electrolysis electrode according to claim 1 .
Citation Information
Patent Citations
Image sensor apparatus
JP2022098944A
Virtual iron tower display system
JP2023062983A
